A Comparison of the Primary Sensory Neurons Used in Olfaction and Vision - Lankford, Colten K.; Laird, Joseph G.; Inamdar, Shivangi M.; Baker, Sheila A. (Frontiers in Cellular Neuroscience, 2020)
Vision, hearing, smell, taste, and touch are the tools used to perceive and navigate the world. They enable us to obtain essential resources such as food and highly desired resources such as mates. Thanks to the investments in biomedical research the molecular unpinning’s of human sensation are rivaled only by our knowledge of sensation in the laboratory mouse. Humans rely heavily on vision whereas mice use smell as their dominant sense. Both modalities have many features in common, starting with signal detection by highly specialized primary sensory neurons – rod and cone photoreceptors for vision, and olfactory sensory neurons for smell. In this chapter we provide an overview of how these two types of primary sensory neurons operate while highlighting the similarities and distinctions.